SOLID IONIC CONDUCTIVE COMPOUND, SOLID ELECTROLYTE CONTAINING SAME, ELECTROCHEMICAL CELL CONTAINING SAME, AND METHOD FOR MANUFACTURING SAME

A solid ionic conductor compound with an argyrodite structure addresses the stability and conductivity issues of conventional solid electrolytes, enhancing lithium ion conductivity and stability in all-solid-state lithium batteries.

JP7617255B2Active Publication Date: 2025-01-17SAMSUNG SDI CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023519535
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-29
Filing Date
2021-06-22
Publication Date
2025-01-17
Estimated Expiration
2041-06-22

AI Technical Summary

Technical Problem

Conventional solid electrolyte materials for all-solid-state lithium batteries are not sufficiently stable to lithium metal and have lower lithium ion conductivity compared to liquid alternatives.

Method used

A solid ionic conductor compound with an argyrodite crystal structure, represented by the formula Li a M x T y P b S c Cl d X e, where M, T, and X are specific elements, is developed to enhance lithium ion conductivity and stability, incorporating elements like Na, K, Rb, Cs, and halogens to improve crystal structure and conductivity.

Benefits of technology

The new solid ionic conductor compound provides improved lithium ion conductivity, stability towards lithium metal, and enhanced cycling characteristics, resulting in higher density and stability of electrochemical cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617255000004
    Figure 0007617255000004
  • Figure 0007617255000005
    Figure 0007617255000005
  • Figure 0007617255000006
    Figure 0007617255000006
Patent Text Reader

Abstract

The present invention is a M x T y P b S c Cl d X e and having an argyrodite crystal structure; a solid electrolyte containing the same; and an electrochemical cell containing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid ionically conductive compound, a solid electrolyte containing the same, a lithium battery containing the same, and a method for producing the same. [Background technology]

[0002] All-solid-state lithium batteries contain a solid electrolyte as an electrolyte. Since all-solid-state lithium batteries do not contain flammable organic solvents, they are excellent in safety.

[0003] Conventional solid electrolyte materials are not stable enough against lithium metal, and their lithium ion conductivity is lower than that of liquid alternatives. Summary of the Invention [Problem to be solved by the invention]

[0004] The problem to be solved by the present invention is to provide a solid ion conductor compound having excellent lithium ion conductivity and softness by having a new composition and crystal structure. [Means for solving the problem]

[0005] According to one aspect, there is provided a solid ionic conductor compound having the argyrodite crystal structure represented by formula 1: Li a M x T y P b S c Cl d X e (chemical formula 1) In the above Chemical Formula 1, M is Na, K, Rb, Cs, Fr or a combination thereof; T is Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or a combination thereof, X is Br, I or a combination thereof, 4 < a < 7, 0 < x < 1, 0 ≦ y < 1, 0 < b ≦ 1, 4 < c ≦ 5, 1 ≦ d + e < 2 and 1 ≦ d / e.

[0006] According to another aspect, a solid electrolyte containing the solid ion conductor compound is provided.

[0007] According to still another aspect, a positive electrode layer including a positive electrode active material layer; a negative electrode layer including a negative electrode active material layer; and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer; are provided, and an electrochemical cell including the solid ion conductor compound is provided.

[0008] According to still another aspect, a step of providing a mixture by contacting a compound containing lithium; a compound containing an element Na, K, Rb, Cs, Fr or a combination thereof; a compound containing phosphorus (P); and a compound containing Cl; a compound containing one or more of the elements Br and I; and a step of heat-treating the mixture in an inert atmosphere to provide a solid ion conductor compound are provided, and a method for producing a solid ion conductor compound is provided.

Advantages of the Invention

[0009] According to one aspect, by including a solid ion conductor compound having improved lithium ion conductivity, softness and stability against lithium metal, an electrochemical cell having high density, improved stability and cycle characteristics is provided.

Brief Description of the Drawings

[0010] [Figure 1] Powder XRD spectra for the solid ion conductor compounds produced in Examples 1 to 6 and Comparative Example 3. [Diagram 2] 1 is a bar graph showing pellet density / powder density ratios for the solid ionic conductor compounds of Examples 1 to 3 and Comparative Examples 1, 2, and 5. [Figure 3A] 1 is a graph showing the discharge capacity by discharge rate of the all-solid-state batteries of Example 7 and Comparative Example 7. [Figure 3B] 1 is a graph showing the discharge capacity retention rates of the all-solid-state batteries of Example 7 and Comparative Example 7. [Figure 4] 1 is a graph showing the change in the amount of H2S generated in the atmosphere for the solid ion conductor compounds produced in Example 5 and Comparative Example 1. [Diagram 5] 1 is a graph showing charge and discharge curves at the beginning and after 100 cycles of the all-solid-state batteries of Example 7 and Comparative Example 7. [Figure 6] 1 is a graph showing the change in discharge capacity of the all-solid-state batteries of Example 7 and Comparative Example 7 after 510 discharges. [Figure 7] FIG. 1 is a schematic diagram of an embodiment of an all-solid-state secondary battery. [Figure 8] FIG. 2 is a schematic diagram of another embodiment of an all-solid-state secondary battery. [Figure 9] FIG. 2 is a schematic diagram of yet another embodiment of an all-solid-state secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Various embodiments are shown in the accompanying drawings. However, the present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the present invention to those skilled in the art. The same reference numerals refer to the same elements throughout.

[0012] It will be apparent that when an element is referred to as being "on" another element, it means that it is directly on top of the other element, or there may be other elements intervening between them. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements between them.

[0013] Terms such as "first", "second", "third" and the like may be used herein to describe various components, components, regions, layers and / or sections, but these components, components, regions, layers and / or sections should not be limited by these terms. These terms are only used to distinguish one component, component, region, layer or section from another component, component, region, layer or section. Thus, a first component, component, region, layer or section described below may also be referred to as a second component, component, region, layer or section without departing from the teachings of this specification.

[0014] The terms used in this specification are for the purpose of describing specific embodiments only and are not intended to limit the inventive concept. As used in this specification, the singular terms include the plural terms including "at least one" unless clearly dictated otherwise. "At least one" should not be construed as being limited to the singular terms. As used herein, the term "and / or" includes any and all combinations of one or more of the listed items. The terms "comprises" and / or "comprising" used in the detailed description specify the presence of the stated features, regions, integers, steps, operations, components, ingredients and / or components and do not exclude the presence or addition of one or more other features, regions, integers, steps, operations, components, ingredients and / or groups thereof.

[0015] Spatially relative terms such as "below," "lower," "bottom," "top," "upper," and "top" may be used herein to easily describe the relationship of one component or feature with respect to other components or features. It will be understood that the spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation depicted in the figures. For example, if the device in the figures were turned upside down, a component described as "below" or "below" the other component or feature would be oriented "above" the other component or feature. Thus, the exemplary term "below" may encompass both an up and down orientation. The device may be oriented in other orientations (rotated 90 degrees or rotated in other directions) and the spatially relative terms used herein may be interpreted accordingly.

[0016] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which this disclosure belongs. It will be further understood that terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant art and the contents of this disclosure, and should not be interpreted as idealized or overly formal.

[0017] Example embodiments are described herein with reference to cross-section views, which are schematic illustrations of idealized embodiments. As such, variations from the shapes of the illustrations as a result, for example, of manufacturing techniques and / or tolerances, are to be expected. Thus, the embodiments described herein should not be construed as limited to the particular shapes of regions as illustrated herein but should include deviations in shapes that, for example, result from manufacturing. For example, a region illustrated or described as being flat may typically have rough and / or non-linear characteristics. Additionally, corners illustrated as sharp may also be rounded. Thus, the regions illustrated in the figures are schematic in nature and the shapes are not intended to illustrate the precise shapes of the regions and are not intended to limit the scope of the claims.

[0018] "Group" means a group in the periodic table of elements according to the 1-18 group classification system of the International Union of Pure and Applied Chemistry ("IUPAC").

[0019] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not currently foreseeable or are unforeseeable may occur to the applicant or a person skilled in the art. Accordingly, the claims that may be filed and amended are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.

[0020] Hereinafter, a solid ion conductor compound according to one or more exemplary embodiments, a solid electrolyte containing the same, an electrochemical cell containing the same, and a method for producing the solid ion conductor compound will be described in more detail.

[0021] [Solid Ion Conductor Compound] A solid ion conductor compound according to one embodiment is represented by the following Chemical Formula 1 and has an alditol crystal structure: Li a M x T y P b S c Cl d X e (Chemical Formula 1) In Chemical Formula 1 above, M is Na, K, Rb, Cs, Fr, or a combination thereof, T is Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or a combination thereof, X is Br, I, or a combination thereof, 4 < a < 7, 0 < x < 1, 0 ≤ y < 1, 0 < b ≤ 1, 4 < c ≤ 5, 1 ≤ d + e < 2, and 1 ≤ d / e.

[0022] According to an embodiment, in Formula 1, M can replace a part of Li in the crystal, and 0 <x≦0.5でもある。

[0023] According to an embodiment, the halogen elements Cl and X may replace a portion of the S element in the crystal.

[0024] The compound represented by Chemical Formula 1 is a crystalline compound having an argyrodite-type crystal structure, in which a portion of Li in the crystal structure is replaced by an element M having a larger diameter than Li, and two or more halogen elements, Cl and X (Br and / or I), replace a portion of S, thereby increasing the disorder of the halogen elements and improving ionic conductivity and softness.

[0025] When a portion of Li in the crystal structure is replaced by an element M with a larger ionic radius, such as Na, the crystal lattice volume increases and the resistance due to the movement of lithium ions within the crystal decreases. When the intracrystalline element S (oxidation number -2) is replaced by a halogen element (oxidation number -1), the ratio of lithium ions that can move within the crystal increases, improving lithium ion conductivity.

[0026] In the case of known argyrodite-type solid electrolytes containing only Cl, there is a problem that the contact with the active material layer material is reduced, resulting in empty spaces in the active material layer, which act as a resistance layer for lithium ion movement, leading to a decrease in ion conductivity and life characteristics. However, the compound represented by Chemical Formula 1, which contains Cl and one or more other halogen elements, has increased flexibility and improved contact with the active material layer material, making it possible to prepare a dense active material layer, resulting in improved lithium ion conductivity and life characteristics. In addition, the replacement of some of the S with halogen has the effect of reducing the amount of harmful H2S gas generated in the atmosphere.

[0027] According to one embodiment, y is also in the range of 0≦y<0.5.

[0028] The compound represented by Chemical Formula 1 has improved moisture stability as a result of a portion of P being replaced with an element T. The element T, for example, Ge, is an inorganic element that has stability against moisture, and thus the structural collapse of the compound in the atmosphere can be suppressed, thereby improving storage stability and processability.

[0029] According to an embodiment, d+e may be in a range of 1.3≦d+e<2. For example, d+e may be in a range of 1.35≦d+e<2.

[0030] According to an embodiment, d / e may be 1≦d / e<18. For example, d / e may be 1≦d / e≦16.

[0031] When the values ​​of d and e satisfy the above formula, the ionic conductivity is improved without precipitation of impurities, and the cycle characteristics can be improved.

[0032] According to an embodiment, the solid ionic conductor compound has a peak intensity (I B ) and the peak intensity at 2θ = 30.09° ± 0.5° (I A ) ratio (I B / I A ) is I B / I A <0.15. For example, B / I A I B / I A It is also ≦0.1.

[0033] Above I A The peak is the main peak of argyrodite type crystals, and the I B The peak is an impurity peak due to the element Br. B / I A If I is less than 0.15, the ionic conductivity is expected to improve. B / I A If it is ≧0.15, the impurities act as a resistance to lithium ion migration, decreasing the lithium ion conductivity.

[0034] According to one embodiment, the solid ion conductor compound represented by Chemical Formula 1 may be represented by the following Chemical Formula 2: (Li 1-x1 M1 x1 ) 7+α-β (P 1-y1 T1 y1 ) α S 6-β (Cl 1-e1 X1 e1 ) β (Chemical Formula 2) In Chemical Formula 2, M1 is Na, K, Rb, Cs, Fr, or a combination thereof, T1 is Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or a combination thereof, X1 is Br, I, or a combination thereof, 0 < x1 < 1, 0 ≦ y1 < 1, 0 < e1 ≦ 0.5, 0 < α ≦ 1, 0 < β ≦ 2.

[0035] In Chemical Formula 2, M1, T1, and X1 respectively refer to the descriptions of M, T, and X in the present application.

[0036] According to one embodiment, M1 may include Na, K, or a combination thereof.

[0037] According to one embodiment, y1 is 0 < y1 ≦ 0.5, and T1 may include Ge, Si, or a combination thereof. For example, T1 may also be Ge.

[0038] According to one embodiment, X1 may also be Br or I. For example, X1 may also be Br.

[0039] According to one embodiment, β is also 1 ≦ β ≦ 2.

[0040] According to one embodiment, the solid ion conductor compound is (Li1-x1 Nor x1 ) 7-β PS 6-β (Cl 1-e1 I e1 ) β 、(The 1-x1 Nor x1 ) 7-β PS 6-β (Cl 1-e1 Br e1 ) β 、(The 1-x1 K x1 ) 7-β PS 6-β (Cl 1-e1 I e1 ) β 、(The 1-x1 K x1 ) 7-β PS 6-β (Cl 1-e1 Br e1 ) β 、(The 1-x1 Rb x1 ) 7-β PS 6-β (Cl 1-e1 I e1 ) β 、(The 1-x1 Rb x1 ) 7-β PS 6-β (Cl 1-e1 Br e1 ) β 、(The 1-x1 Cs x1 ) 7-β PS 6-β (Cl 1-e1 I e1 ) β 、(The 1-x1 Cs x1 ) 7-β PS 6-β (Cl 1-e1 Br e1 ) β 、(The 1-x1 Fr x1 ) 7-β PS 6-β (Cl 1-e1 I e1 ) β または(Li 1-x1 Fr x1 ) 7-β PS6-β (Cl 1-e1 Br e1 ) β In this case, 0 <x1<1,0<e1≦0.5,0<β≦2である。

[0041] According to one embodiment, the solid ionic conductor compound is (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 I e1 ) β , (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 Br e1 ) β , (Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 I e1 ) β , (Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 Br e1 ) β , (Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 I e1 ) β , (Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ge y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Si y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Si y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P1-y1 Yes y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Yes y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 Yes y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 Yes y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Yes y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Yes y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Yes y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li1-x1 Fr x1 ) 7+α-β (P 1-y1 Si y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β(Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Sc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Y y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Y y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P1-y1 Y y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Y y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Y y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Y y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Y y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Y y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Y y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Frx1 ) 7+α-β (P 1-y1 Y y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β、 (Li 1-x1 On x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 On x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 No.e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 You y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β、 (Li 1-x1 On x1 ) 7+α-β (P 1-y1 Zr y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 On x1 ) 7+α-β (P 1-y1 Zr y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Zr y1) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Zr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Zr y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Zr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Zr y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Zr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Zr y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 )7+α-β (P 1-y1 Zr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 Br e1) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Hf y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 V y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 V y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 V y1 ) αS 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 V y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 V y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 V y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 V y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 V y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 V y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1V y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li1-x1 Cs x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Nb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β(Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ta y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Tay1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1Cs x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Cr y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Mo y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Moy1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Csx1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 W y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Mn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Mn y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Tc y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Re y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Re y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Fe y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ru y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ru y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Os y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Os y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Os y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Os y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Os y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Os y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Axis y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β ,(If 1-x1 Cs x1 ) 7+α-β (P 1-y1 Axis y1 ) α WITH 6-β (Cl 1-e1 Br e1 ) β ,(If 1-x1 Fr x1 ) 7+α-β (P 1-y1 Axis y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β ,(If 1-x1 Fr x1 ) 7+α-β (P 1-y1 Axis y1 ) α WITH 6-β (Cl 1-e1 Br e1 ) β、 (If 1-x1 On x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β ,(If 1-x1 On x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 Br e1 ) β ,(If 1-x1 TO x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 ANDe1 ) β ,(If 1-x1 TO x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 Br e1 ) β ,(If 1-x1 Rb x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β ,(If 1-x1 Rb x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 Br e1 ) β ,(If 1-x1 Cs x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β ,(If 1-x1 Cs x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 Br e1 ) β ,(If 1-x1 Fr x1 ) 7+α-β (P 1-y1 What y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β ,(If 1-x1 Fr x1 ) 7+α-β (P 1-y1 What y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Rh y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Ir y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Ir y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ir y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 And y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 And y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 And y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 And y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 And y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 And y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 And y1 )α WITH 6-β (Cl 1-e1 No. e1 ) β、 (Li 1-x1 On x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 On x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Nor y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β、 (Li 1-x1 On x1 ) 7+α-β (P 1-y1 Pd y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 On x1 ) 7+α-β (P 1-y1 Pd y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Pd y1 ) α WITH 6-β (Cl 1-e1 ANDe1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Pd y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Pd y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Pd y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Pd y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Pd y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Pd y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Pd y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Pt y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Cu y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Cu y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Cu y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(The 1-x1 K x1 ) 7+α-β (P 1-y1 The y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(The 1-x1 Rb x1 ) 7+α-β (P 1-y1 The y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(The 1-x1 Rb x1 ) 7+α-β (P 1-y1 The y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(The 1-x1 Cs x1 ) 7+α-β (P 1-y1 The y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(The 1-x1 Cs x1 ) 7+α-β (P 1-y1 The y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(The 1-x1 Fr x1 ) 7+α-β (P 1-y1 The y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(The 1-x1 Fr x1 ) 7+α-β (P 1-y1 The y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 No x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 No x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ag y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Au y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Au y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Zn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Cd y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Cd y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Hg y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Al y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Al y1 )α WITH 6-β (Cl 1-e1 No. e1 ) β、 (Li 1-x1 On x1 ) 7+α-β (P 1-y1 Him y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 On x1 ) 7+α-β (P 1-y1 Him y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Him y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Him y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 Him y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 Him y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Ga y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Ga y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ga y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Ga y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 In y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 In y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 No x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 No x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Tl y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Sn y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Sn y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Pb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 As y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 As y1 )α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Rb x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Cs x1) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Sb y1 ) α S 6-β (Cl 1-e1 Br e1 ) β、 (Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Bi y1 ) α S 6-β (Cl 1-e1 I e1 ) β 、(Li 1-x1 Na x1 ) 7+α-β (P 1-y1 Bi y1 ) α S 6-β (Cl 1-e1 Br e1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Bi y1 ) α S 6-β (Cl 1-e1 Ie1 ) β 、(Li 1-x1 K x1 ) 7+α-β (P 1-y1 Would y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 Would y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Number x1 ) 7+α-β (P 1-y1 Would y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Would y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、(Li 1-x1 Cs x1 ) 7+α-β (P 1-y1 Would y1 ) α WITH 6-β (Cl 1-e1 No. e1 ) β 、(Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Would y1 ) α WITH 6-β (Cl 1-e1 AND e1 ) β 、or (Li 1-x1 Fr x1 ) 7+α-β (P 1-y1 Would y1 )α S 6-β (Cl 1-e1 Br e1 ) β In this case, 0 <x1<1,0≦y1<1,0<e1≦0.5,0<α≦1,0<β≦2である。

[0042] According to an embodiment, the solid ionic conductor compound represented by Formula 1 may be represented by Formula 3 below: Li 7-x2+y2-d2-e2 M2 x2 P 1-y2 T2 y2 S 6-d2-e2 Cl d2 X e2 (Chemical formula 3) In the above Chemical Formula 3, M2 is Na, K, Rb, Cs, Fr or a combination thereof; T2 is Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or a combination thereof; X2 is Br, I or a combination thereof; 0 <x2<1、0≦y2<1、1≦d2+e2<2、d2 / e2≧1である。

[0043] In the above Chemical Formula 3, M2, T2, and X2 refer to the descriptions of M, T, and X in this application, respectively.

[0044] According to one embodiment, x2, y2 and d2+e2 are each 0 <x2≦0.5、0≦y2<0.5、1.3≦d2+e2<2でもある。

[0045] According to an embodiment, d2 and e2 are 0.8≦d2<2 and 0.8≦e2<2, respectively. <e2≦0.8でもある。

[0046] According to one embodiment, the solid ionic conductor compound is Li 5.6 Na 0.05 P.S. 4.65Cl 1.25 AND 0.1 、Li 5.47 On 0.03 P.S 4.5 Cl 1.4 AND 0.1 、Li 5.47 On 0.03 P.S 4.5 Cl 1.4 No. 0.1 、Li 5.37 On 0.03 P.S 4.4 Cl 1.4 No. 0.2 、Li 5.57 On 0.03 P 0.9 Ge 0.1 WITH 4.5 ClBr 0.5 、Li 5.37 On 0.03 P.S 4.4 Cl 0.8 No. 0.8 、Li 5.35 On 0.05 P.S 4.4 Cl 1.5 AND 0.1 、Li 5.47 On 0.03 P.S 4.5 Cl 1.3 No. 0.2 、Li 5.56 On 0.04 P.S 4.6 Cl 1.3 No. 0.1 、Li 5.57 On 0.03 P 0.9 Ge 0.1 WITH 4.5 Cl 0.8 No. 0.7 、Li 5.57 On 0.03 P 0.8 Ge 0.2 WITH 4.5 Cl 1.4 AND 0.1 Or Li 5.57 On 0.03 P 0.8 Yes 0.2 WITH 4.4 Cl 1.4 No. 0.2 Even so.

[0047] The solid ion conductor compound provides improved lithium ion conductivity. The solid ion conductor compound represented by Chemical Formula 1 provides an ion conductivity of 3.4 mS / cm or more, 4.0 mS / cm or more, 4.5 mS / cm or more, 5.0 mS / cm or more, or 5.5 mS / cm or more at room temperature, for example, at about 25° C. In addition, the solid ion conductor compound provides an ion conductivity of 3.4 mS / cm to 8.0 mS / cm, 4.0 mS / cm to 8.0 mS / cm, 4.5 mS / cm to 8.0 mS / cm, 5.0 mS / cm to 8.0 mS / cm, 3.4 mS / cm to 7.9 mS / cm, 3.4 mS / cm to 7.8 mS / cm, or 3.4 mS / cm to 7.7 mS / cm at room temperature, for example, at about 25° C.

[0048] According to an embodiment, the solid ion conductor compound has a pellet density / powder density ratio of 85% or more.

[0049] Here, the pellet density is 4 ton / cm after the solid ion conductor compound powder is made into a pellet. 2 After pressing for 2 minutes at a pressure of 0.1 MPa, the density was measured and the powder density was calculated using density functional theory as known in the art.

[0050] [Solid electrolyte] A solid electrolyte according to another embodiment includes a solid ion conductor compound represented by the above-mentioned Chemical Formula 1. By including such a solid ion conductor compound, the solid electrolyte has high ionic conductivity, high chemical stability, and a reduced amount of harmful gas H2S emission. The solid electrolyte including the solid ion conductor compound represented by Chemical Formula 1 can provide improved stability against air and electrochemical stability against lithium metal. Therefore, the solid ion conductor compound represented by Chemical Formula 1 can be used, for example, as a solid electrolyte in an electrochemical cell.

[0051] The solid electrolyte may further include a conventional solid electrolyte in addition to the solid ion conductor compound represented by Chemical Formula 1. For example, the solid electrolyte may further include a conventional sulfide-based solid electrolyte and / or an oxide-based solid electrolyte. Examples of the conventional solid ion conductor compounds that may be further included include Li2O-Al2O3-TiO2-P2O5 (LATP), LISICON (Lithium SuperIonic Conductor), LIPON (Li 3-y PO 4-x N x ,0 <y<3,0<x<4)、Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S4), Li2S, Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, Li2S-B2S5, and Li2S-Al2S5, but are not necessarily limited thereto, and any usable in the art may be used.

[0052] The solid electrolyte may be in the form of a powder or a molded product. The molded solid electrolyte may be in the form of, for example, a pellet, a sheet, a thin film, etc., but is not necessarily limited thereto, and may have various forms depending on the application.

[0053] [Electrochemical cell] According to another embodiment, the electrochemical cell includes a positive electrode layer including a positive electrode active material layer; a negative electrode layer including a negative electrode active material layer; an electrolyte layer disposed between the positive electrode layer and the negative electrode layer; and the solid ion conductor compound described above.

[0054] According to an embodiment, the positive electrode active material layer may include the solid ion conductor compound. In this case, the solid ion conductor compound has an average particle size D of 2 μm or less. 50 In this case, the D 50 means the diameter of particles corresponding to 50% by volume in the accumulated particle size distribution. When the average particle size of the solid ion conductor compound contained in the positive electrode active material layer exceeds 2 μm, it is difficult to achieve dense packing of particles, and the capacity characteristics are reduced during charging and discharging of the cell.

[0055] According to an embodiment, the electrolyte layer may include the solid ion conductor compound. In this case, the solid ion conductor compound has an average particle size D of 5 μm or less. 50 Since the average particle size of the solid ion conductor compound in the electrolyte layer is 5 μm or less, the density and uniformity of the electrolyte layer are improved and the occurrence of defects such as pinholes in the electrolyte layer is suppressed, resulting in improved life characteristics of the cell.

[0056] According to an embodiment, the positive electrode active material layer and the electrolyte layer may include the solid ion conductor compound.

[0057] The electrochemical cell includes the solid ion conductor compound, which improves the lithium ion conductivity and chemical stability of the electrochemical cell.

[0058] The electrochemical cell may be, for example, an all-solid-state secondary battery, a secondary battery containing a liquid electrolyte, or a lithium-air battery, but is not necessarily limited thereto, and any electrochemical cell available in the art may be used.

[0059] The all-solid-state secondary battery will be described in more detail below.

[0060] [All-solid-state secondary battery: Type 1] The all-solid-state secondary battery may include the solid ion conductor compounds described above.

[0061] The all-solid-state secondary battery includes, for example, a positive electrode layer including a positive electrode active material layer; a negative electrode layer including a negative electrode active material layer; and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer; and the positive electrode active material layer and / or the electrolyte layer may include the above-mentioned solid ion conductor compound.

[0062] An all-solid-state secondary battery according to an embodiment may be prepared as follows.

[0063] (Solid electrolyte layer) First, a solid electrolyte layer is provided.

[0064] The solid electrolyte layer can be manufactured by mixing the above-mentioned solid ion conductor compound with a binder and drying it, or by rolling the powder of the solid ion conductor compound represented by Chemical Formula 1 into a certain shape at a pressure of 1 to 10 tons. The above-mentioned solid ion conductor compound is used as the solid electrolyte.

[0065] The solid electrolyte has an average particle size of, for example, 0.5 μm to 20 μm. When the solid electrolyte has such an average particle size, the binding property is improved during the formation of a sintered body, and the ionic conductivity and life characteristics of the solid electrolyte particles can be improved.

[0066] The thickness of the solid electrolyte layer is also 10 μm to 200 μm. When the solid electrolyte layer has such a thickness, a sufficient migration speed of lithium ions is guaranteed, and as a result, high ion conductivity is obtained.

[0067] The solid electrolyte layer may further include a solid electrolyte such as a conventional sulfide-based solid electrolyte and / or an oxide-based solid electrolyte in addition to the above-mentioned solid ion conductor compound.

[0068] The conventional sulfide-based solid electrolyte may include, for example, lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide, or a combination thereof. The conventional sulfide-based solid electrolyte particles may include Li2S, P2S5, SiS2, GeS2, B2S3, or a combination thereof. The conventional sulfide-based solid electrolyte particles may also be Li2S or P2S5. The conventional sulfide-based solid electrolyte particles are known to have a higher lithium ion conductivity than other inorganic compounds. For example, the conventional sulfide-based solid electrolyte includes Li2S and P2S5. When the sulfide solid electrolyte material constituting the conventional sulfide-based solid electrolyte includes Li2S-P2S5, the mixed molar ratio of Li2S:P2S5 is, for example, in the range of about 50:50 to about 90:10. In addition, Li3PO4, halogen, halogen compound, Li 2+2x Zinc 1-x GeO4("LISICON"),Li 3+y PO 4-x Nx( "LIPON" 3.25 Ge 0.25 P 0.75 S4(“ThioLISICON”),Li2O-Al2O3-TiO2-P2O 5( An inorganic solid electrolyte prepared by adding an inorganic solid electrolyte such as Li2S-P2S5, SiS2, GeS2, B2S3, or a combination thereof, such as "LATP" may be used as a conventional sulfide solid electrolyte. Non-limiting examples of conventional sulfide solid electrolyte materials include Li2S-P2S5; Li2S-P2S5-LiX (X is a halogen element); Li2S-P2S5-Li2O; Li2S-P2S5-Li2O-LiI; Li2S-SiS2; Li2S-SiS2-LiI; Li2S-SiS2-LiBr; Li2S-SiS2-LiCl; Li2S-SiS2-B2S3-LiI; Li2S-SiS2-P2S5-LiI; Li2S-B2S3; Li2S-P2S5-Z m S n (m and n are positive numbers, and Z is Ge, Zn, or G); Li2S-GeS2; Li2S-SiS2-Li3PO4; and Li2S-SiS2-Li p MO q (wherein p and q are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In). In this regard, a conventional sulfide-based solid electrolyte material can be prepared by treating a starting material of a sulfide-based solid electrolyte material (e.g., Li2S, P2S5, etc.) by a melt quenching method, a mechanical milling method, etc. Also, a calcinations process can be performed after the treatment.

[0069] The binder contained in the solid electrolyte layer may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polyvinyl alcohol, or any other binder used in the art, but is not limited thereto. The binder of the solid electrolyte layer may be the same as or different from the binders of the positive and negative electrode layers.

[0070] (Positive electrode layer) Then the positive electrode layer is applied.

[0071] The positive electrode layer can be produced by forming a positive electrode active material layer containing a positive electrode active material on a current collector. The positive electrode active material has an average particle size of, for example, 2 μm to 10 μm.

[0072] The positive electrode active material can be any material that is commonly used in secondary batteries without any restrictions. For example, lithium transition metal oxides and transition metal sulfides can be used. For example, one or more of composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof can be used. Specific examples include Li a A 1-b B 1 b D 1 2 (wherein 0.90≦a≦1.8 and 0≦b≦0.5); Li a E 1-b B 1 b O 2-c D 1 c (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05); LiE 2-b B 1 b O 4-c D 1 c (wherein, 0≦b≦0.5, 0≦c≦0.05); Li a Ni1-b-c Co b B 1 c D 1 α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Co b B 1 c O 2-α F 1 α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Co b B 1 c O 2-α F 1 α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B 1 c D 1 α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Mn b B 1 c O 2-α F 1 α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B 1 c O 2-α F 1 2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G dO2 (wherein, 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0.001≦d≦0.1); Li a Ni b Co c Mn d GeO2 (wherein, 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, 0.001≦e≦0.1); Li a NiG b O2 (wherein, 0.90≦a≦1.8, 0.001≦b≦0.1); Li a CoG b O2 (wherein, 0.90≦a≦1.8, 0.001≦b≦0.1); Li a MnG b O2 (wherein, 0.90≦a≦1.8, 0.001≦b≦0.1); Li a Mn2G b O4 (wherein 0.90≦a≦1.8, 0.001≦b≦0.1); QO2; QS2; LiQS2; V2O5; LiV2O2; LiIO2; LiNiVO4; Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) A compound represented by any one of the chemical formulas Fe2(PO4)3(0≦f≦2);LiFePO4 may be used. In the above chemical formula, A is Ni, Co, Mn, or a combination thereof, and B is 1 is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or combinations thereof, and D 1 is O, F, S, P, or a combination thereof, E is Co, Mn, or a combination thereof, and F 1 is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I is Cr, V, Fe, Sc, Y, or a combination thereof; J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof. For example, LiCoO2, LiMn x O 2x (x=1,2), LiNi 1-x Mnx O 2x (0 <x<1)、Ni 1-x-y Co x Mn y O2(0≦x≦0.5,0≦y≦0.5), Ni 1-x-y Co x Al y O2(0≦x≦0.5,0≦y≦0.5), LiFePO4, TiS2, FeS2, TiS3, FeS3, etc.

[0073] It is also possible to use a compound in which a coating layer is added to the surface of such a compound, and it is also possible to use a mixture of the above-mentioned compound and a compound to which a coating layer is added. The coating layer added to the surface of such a compound includes, for example, a coating element compound such as an oxide, hydroxide, oxyhydroxide, oxycarbonate, or hydroxycarbonate of a coating element of a coating element. The compound forming such a coating layer is amorphous or crystalline. The coating element contained in the coating layer is Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method of forming the coating layer is selected within a range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, spray coating, immersion, etc. The specific coating method is well understood by those skilled in the art, so a detailed description will be omitted.

[0074] The positive electrode active material includes, for example, a lithium salt of a transition metal oxide having a layered rock salt type structure among the above-described lithium transition metal oxides. The "layered rock salt type structure" is, for example, a structure in which oxygen atom layers and metal atom layers are regularly arranged alternately in the <111> direction of a cubic rock salt type structure, whereby each atom layer forms a two-dimensional plane. The "cubic rock salt type structure" indicates a sodium chloride type (NaCl type) structure which is a kind of crystal structure. Specifically, it indicates a structure in which face-centered cubic lattices (fcc) formed by cations and anions are displaced from each other by about 1 / 2 of the ridge of the unit lattice. Such a lithium transition metal oxide having a layered rock salt type structure is, for example, LiNi x Co y Al z O2 (NCA) or LiNi x Co y Mn z O2 (NCM) (0 < x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1), etc., which are ternary lithium transition metal oxides. When the positive electrode active material includes a ternary lithium transition metal oxide having a layered rock salt type structure, the energy density and thermal stability of the all-solid-state secondary battery 1 are further improved.

[0075] The positive electrode active material is also covered by a coating layer as described above. Any coating layer can be used as long as it is known as a coating layer for the positive electrode active material of an all-solid-state secondary battery. The coating layer is, for example, Li2O-ZrO2 (LZO), etc.

[0076] When the positive electrode active material is a ternary lithium transition metal oxide such as NCA or NCM and contains nickel (Ni), it is possible to increase the capacity density of the all-solid-state secondary battery and reduce the metal elution of the positive electrode active material in the charged state. As a result, the cycle characteristics of the all-solid-state secondary battery in the charged state are improved.

[0077] The shape of the positive electrode active material is, for example, a particle shape such as a perfect sphere or an oval sphere. The particle size of the positive electrode active material is not particularly limited, and is within the range applicable to the positive electrode active material of a conventional all-solid-state secondary battery. The content of the positive electrode active material in the positive electrode layer is also not particularly limited, and is within the range applicable to the positive electrode layer of a conventional all-solid-state secondary battery. The content of the positive electrode active material in the positive electrode active material layer is, for example, 50 to 95% by weight.

[0078] The positive electrode active material layer may further include the above-mentioned solid ion conductor compound. For example, the positive electrode active material layer and the solid electrolyte layer may simultaneously include the above-mentioned solid ion conductor compound. For example, when the positive electrode active material layer includes the above-mentioned solid ion conductor compound, the solid electrolyte layer may not include the above-mentioned solid ion conductor compound.

[0079] The positive electrode active material layer contains a binder, such as styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene.

[0080] The positive electrode active material layer includes a conductive material, such as graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or metal powder.

[0081] The positive electrode active material layer may further include additives such as a filler, a coating agent, a dispersant, and an ion conductive assistant, in addition to the above-mentioned positive electrode active material, solid electrolyte, binder, and conductive material.

[0082] As the filler, coating agent, dispersant, ion conductive assistant, and the like contained in the positive electrode active material layer, known materials generally used for electrodes of all-solid-state secondary batteries can be used.

[0083] The positive electrode current collector is, for example, a plate or foil made of aluminum (Al), indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector is optional.

[0084] The positive electrode current collector may further include a carbon layer disposed on one or both sides of the metal substrate. By additionally disposing the carbon layer on the metal substrate, the metal of the metal substrate may be prevented from being corroded by the solid electrolyte contained in the positive electrode layer, and the interface resistance between the positive electrode active material layer and the positive electrode current collector may be reduced. The carbon layer may have a thickness of, for example, 1 μm to 5 μm. If the carbon layer is too thin, it is difficult to completely block the contact between the metal substrate and the solid electrolyte. If the carbon layer is too thick, the energy density of the all-solid-state secondary battery may be reduced. The carbon layer may include amorphous carbon, crystalline carbon, etc.

[0085] (Negative electrode layer) Then the negative electrode layer is applied.

[0086] The negative electrode layer may be manufactured in the same manner as the positive electrode layer, except that a negative electrode active material is used instead of a positive electrode active material. The negative electrode layer may be manufactured by forming a negative electrode active material layer including the negative electrode active material on a negative electrode current collector.

[0087] The negative electrode active material layer may further include the solid ion conductor compound described above.

[0088] The negative electrode active material can be lithium metal, a lithium metal alloy, or a combination thereof.

[0089] In addition to lithium metal, a lithium metal alloy, or a combination thereof, the negative electrode active material layer may further contain a conventional negative electrode active material. The conventional negative electrode active material may include, for example, one or more selected from the group consisting of metals alloyable with lithium, transition metal oxides, non-transition metal oxides, and carbon-based materials. Metals alloyable with lithium include, for example, Ag, Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y alloy (where Y is an alkali metal, alkaline earth metal, Group 13 element, Group 14 element, transition metal, rare earth element, or a combination thereof, and is not Si), Sn-Y alloy (where Y is an alkali metal, alkaline earth metal, Group 13 element, Group 14 element, transition metal, rare earth element, or a combination thereof, and is not Sn), and the like. Examples of the element Y also include Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof. Transition metal oxides include, for example, lithium titanate oxide, vanadium oxide, lithium vanadate oxide, and the like. Non-transition metal oxides include, for example, SnO2, SiOx (0 < x < 2), and the like. Carbon-based materials include, for example, crystalline carbon, amorphous carbon, or a mixture thereof. Crystalline carbon is also graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and the amorphous carbon is also soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0090] 7, an all-solid-state secondary battery 40 according to an embodiment includes a solid electrolyte layer 30, a positive electrode layer 10 disposed on one side of the solid electrolyte layer 30, and a negative electrode layer 20 disposed on the other side of the solid electrolyte layer 30. The positive electrode layer 30 includes a positive electrode active material layer 12 in contact with the solid electrolyte layer 30 and a positive electrode current collector 11 in contact with the positive electrode active material layer 12, and the negative electrode layer 20 includes a negative electrode active material layer 22 in contact with the solid electrolyte layer 30 and a negative electrode current collector 21 in contact with the negative electrode active material layer 22. The all-solid-state secondary battery 40 is completed, for example, by forming the positive electrode active material layer 12 and the negative electrode active material layer 22 on both sides of the solid electrolyte layer 30, and forming the positive electrode current collector 11 and the negative electrode current collector 21 on the positive electrode active material layer 12 and the negative electrode active material layer 22, respectively. Alternatively, the all-solid-state secondary battery 40 is completed by, for example, laminating the negative electrode active material layer 22, the solid electrolyte layer 30, the positive electrode active material layer 12, and the positive electrode current collector 11 in this order on the negative electrode current collector 21.

[0091] [All-solid-state secondary battery: Type 2] 8 and 9, the all-solid-state secondary battery 1 includes, for example, a positive electrode layer 10 including a positive electrode active material layer 12 disposed on a positive electrode current collector 11; a negative electrode layer 20 including a negative electrode active material layer 22 disposed on a negative electrode current collector 21; and an electrolyte layer 30 disposed between the positive electrode layer 10 and the negative electrode layer 20, and the positive electrode active material layer 12 and / or the electrolyte layer 30 may include the above-mentioned solid ion conductor compound.

[0092] According to another embodiment, the all-solid-state secondary battery may be prepared as follows.

[0093] The positive electrode layer and the solid electrolyte layer are manufactured in the same manner as in the above-mentioned all-solid-state secondary battery.

[0094] (Negative electrode layer) Then the negative electrode layer is applied.

[0095] 8 and 9, the negative electrode layer 20 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on the negative electrode current collector. The negative electrode active material layer 22 includes, for example, a negative electrode active material and a binder.

[0096] The negative electrode active material contained in the negative electrode active material layer 22 has, for example, a particulate shape. The particulate negative electrode active material has an average particle size of, for example, 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, or 900 nm or less. The particulate negative electrode active material has an average particle size of, for example, 10 nm to 4 μm or less, 10 nm to 3 μm or less, 10 nm to 2 μm or less, 10 nm to 1 μm or less, or 10 nm to 900 nm or less. When the negative electrode active material has an average particle size in such a range, reversible absorbing and / or desorbing of lithium during charging and discharging is further facilitated. The average particle size of the negative electrode active material is, for example, a median diameter D measured using a laser type particle size distribution meter. 50 It is.

[0097] The negative electrode active material contained in the negative electrode active material layer 22 includes, for example, one or more selected from a carbon-based negative electrode active material and a metal or semimetal negative electrode active material.

[0098] The carbon-based negative electrode active material is, in particular, amorphous carbon. Examples of amorphous carbon include, but are not limited to, carbon black (CB), acetylene black (AB), furnace black (FB), ketjen black (KB), graphene, etc., and any material that is classified as amorphous carbon in the art can be used. Amorphous carbon is carbon that has no crystallinity or has very low crystallinity, and is classified as crystalline carbon or graphite-based carbon.

[0099] The metal or metalloid negative electrode active material includes, but is not necessarily limited to, one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn), and any metal or metalloid negative electrode active material that forms an alloy or compound with lithium in the art can be used. For example, nickel (Ni) is not a metal negative electrode active material because it does not form an alloy with lithium.

[0100] The negative electrode active material layer 22 includes one type of negative electrode active material among such negative electrode active materials, or includes a mixture of a plurality of different negative electrode active materials. For example, the negative electrode active material layer 22 includes only amorphous carbon, or includes one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the negative electrode active material layer 22 includes a mixture of amorphous carbon and one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The mixing ratio of the mixture of amorphous carbon and gold, etc., in terms of weight ratio, is, for example, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1, but is not necessarily limited to such ranges and is selected depending on the required characteristics of the all-solid-state secondary battery 1. When the negative electrode active material has such a composition, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.

[0101] The negative electrode active material contained in the negative electrode active material layer 22 includes, for example, a mixture of first particles made of amorphous carbon and second particles made of a metal or a metalloid. The metal or metalloid includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The metalloid is alternatively a semiconductor. The content of the second particles is 8 to 60 wt%, 10 to 50 wt%, 15 to 40 wt%, or 20 to 30 wt%, based on the total weight of the mixture. When the second particles have a content in such a range, for example, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.

[0102] The binder contained in the negative electrode active material layer 22 is, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited thereto, and any binder used in the relevant technical field can be used. The binder can be composed of a single binder or a plurality of different binders.

[0103] The negative electrode active material layer 22 contains a binder, so that the negative electrode active material layer 22 is stabilized on the negative electrode current collector 21. In addition, cracks in the negative electrode active material layer 22 are suppressed despite changes in volume and / or relative position of the negative electrode active material layer 22 during charging and discharging. For example, if the negative electrode active material layer 22 does not contain a binder, the negative electrode active material layer 22 may be easily separated from the negative electrode current collector 21. When the negative electrode active material layer 22 is detached from the negative electrode current collector 21, the negative electrode current collector 21 comes into contact with the solid electrolyte layer 30 at the exposed portion of the negative electrode current collector 21, increasing the possibility of short circuit occurrence. The negative electrode active material layer 22 is prepared, for example, by applying a slurry in which materials constituting the negative electrode active material layer 22 are dispersed onto the negative electrode current collector 21 and drying it. By including a binder in the negative electrode active material layer 22, the negative electrode active material can be stably dispersed in the slurry. For example, when the slurry is applied onto the negative electrode current collector 21 by a screen printing method, clogging of the screen (for example, clogging due to aggregates of the negative electrode active material) can be suppressed.

[0104] The negative electrode active material layer 22 may further contain additives used in conventional all-solid-state secondary batteries 1, such as a filler, a coating agent, a dispersant, an ion-conducting assistant, and the like.

[0105] The thickness of the negative electrode active material layer 22 is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of the thickness of the positive electrode active material layer 12. The thickness of the negative electrode active material layer 22 is, for example, 1 μm to 20 μm, 2 μm to 10 μm, or 3 μm to 7 μm. If the thickness of the negative electrode active material layer 22 is excessively thin, lithium dendrites formed between the negative electrode active material layer 22 and the negative electrode current collector 21 collapse the negative electrode active material layer 22, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the thickness of the negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 decreases, and the internal resistance of the all-solid-state secondary battery 1 due to the negative electrode active material layer 22 increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0106] If the thickness of the negative electrode active material layer 22 is reduced, for example, the charge capacity of the negative electrode active material layer 22 is also reduced. The charge capacity of the negative electrode active material layer 22 is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 5% or less, or 2% or less compared to the charge capacity of the positive electrode active material layer 12. The charge capacity of the negative electrode active material layer 22 is, for example, 0.1% to 50%, 0.1% to 40%, 0.1% to 30%, 0.1% to 20%, 0.1% to 10%, 0.1% to 5%, or 0.1% to 2% compared to the charge capacity of the positive electrode active material layer 12. If the charge capacity of the negative electrode active material layer 22 is excessively small, the thickness of the negative electrode active material layer 22 becomes very thin, and thus lithium dendrites formed between the negative electrode active material layer 22 and the negative electrode current collector 21 during repeated charge and discharge processes collapse the negative electrode active material layer 22, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the charge capacity of the negative electrode active material layer 22 increases excessively, the energy density of the all-solid-state secondary battery 1 decreases and the internal resistance of the all-solid-state secondary battery 1 due to the negative electrode active material layer 22 increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0107] The charge capacity of the positive electrode active material layer 12 is obtained by multiplying the charge capacity density (mAh / g) of the positive electrode active material by the mass of the positive electrode active material in the positive electrode active material layer 12. When multiple types of positive electrode active materials are used, the charge capacity density mass value is calculated for each positive electrode active material, and the sum of these values ​​is the charge capacity of the positive electrode active material layer 12. The charge capacity of the negative electrode active material layer 22 is also calculated in a similar manner. That is, the charge capacity of the negative electrode active material layer 22 is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the negative electrode active material layer 22. When multiple types of negative electrode active materials are used, the charge capacity density mass value is calculated for each negative electrode active material, and the sum of these values ​​is the capacity of the negative electrode active material layer 22. Here, the charge capacity density of the positive electrode active material and the negative electrode active material is a capacity estimated using an all-solid-state half-cell using lithium metal as a counter electrode. The charge capacities of the positive electrode active material layer 12 and the negative electrode active material layer 22 are directly measured by measuring the charge capacity using an all-solid-state half-cell. The charge capacity density is obtained by dividing the measured charge capacity by the mass of each active material. Alternatively, the charge capacity of the positive electrode active material layer 12 and the negative electrode active material layer 22 is also the initial charge capacity measured during the first cycle of charging.

[0108] 9, the all-solid-state secondary battery 1a may further include, for example, a metal layer 23 disposed between the negative electrode current collector 21 and the negative electrode active material layer 22. The metal layer 23 includes lithium or a lithium alloy. Thus, the metal layer 23 acts, for example, as a lithium reservoir. The lithium alloy may be, for example, a Li-Al alloy, a Li-Sn alloy, a Li-In alloy, a Li-Ag alloy, a Li-Au alloy, a Li-Zn alloy, a Li-Ge alloy, a Li-Si alloy, etc., but is not limited thereto, and any alloy used as a lithium alloy in the art may be used. The metal layer 23 may be made of one of such alloys or lithium, or may be made of a plurality of alloys.

[0109] The thickness of the metal layer 23 is not particularly limited, and may be, for example, 1 μm to 1000 μm, 1 μm to 500 μm, 1 μm to 200 μm, 1 μm to 150 μm, 1 μm to 100 μm, or 1 μm to 50 μm. If the thickness of the metal layer 23 is too thin, it is difficult for the metal layer 23 to perform the role of a lithium reservoir. If the thickness of the metal layer 23 is too thick, the mass and volume of the all-solid-state secondary battery 1 increase, and there is a possibility that the cycle characteristics may deteriorate. The metal layer 23 may be, for example, a metal foil having a thickness in such a range.

[0110] The metal layer 23 in the all-solid-state secondary battery 1a is, for example, disposed between the negative electrode current collector 21 and the negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1, or is precipitated between the negative electrode current collector 21 (21, 21a, 21b) and the negative electrode active material layer 22 by charging after assembling the all-solid-state secondary battery 1. When the metal layer 23 is disposed between the negative electrode current collector 21 and the negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1a, the metal layer 23 is a metal layer containing lithium, and therefore acts as a lithium reservoir. For example, a lithium foil is disposed between the negative electrode current collector 21 and the negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1a. This further improves the cycle characteristics of the all-solid-state secondary battery 1a including the metal layer 23. When the metal layer 23 is precipitated by charging after assembling the all-solid-state secondary battery 1a, the all-solid-state secondary battery 1a does not include the metal layer 23 when assembled, and therefore the energy density of the all-solid-state secondary battery 1a is increased. For example, when the all-solid-state secondary battery 1 is charged, it is charged beyond the charge capacity of the anode active material layer 22. That is, the anode active material layer 22 is overcharged. At the beginning of charging, lithium is absorbed in the anode active material layer 22. The anode active material contained in the anode active material layer 22 forms an alloy or a compound with the lithium ions transferred from the cathode layer 10. If the anode active material layer 22 is charged beyond its capacity, for example, lithium is deposited on the back surface of the anode active material layer 22, i.e., between the anode current collector 21 and the anode active material layer 22, and a metal layer corresponding to the metal layer 23 is formed by the deposited lithium. The metal layer 23 is a metal layer mainly composed of lithium (i.e., metallic lithium). Such a result is obtained, for example, because the anode active material contained in the anode active material layer 22 is composed of a material that forms an alloy or a compound with lithium. During discharge, the anode active material layer 22 and the metal layer 23, i.e., the lithium in the metal layer is ionized and moves toward the cathode layer 10. Therefore, lithium can be used as the negative electrode active material in the all-solid-state secondary battery 1a. In addition, the negative electrode active material layer 22 covers the metal layer 23, and therefore serves as a protective layer for the metal layer 23 and also serves to suppress the precipitation growth of lithium dendrites. Therefore, short circuits and capacity reduction of the all-solid-state secondary battery 1a are suppressed, and as a result, the cycle characteristics of the all-solid-state secondary battery 1a are improved.In addition, when the metal layer 23 is disposed by charging after the assembly of the all-solid-state secondary battery 1a, the negative electrode current collector 21, the negative electrode active material layer 22, and the region therebetween are, for example, Li-free regions that do not contain lithium (Li) in the initial state or post-discharge state of the all-solid-state secondary battery 1a.

[0111] The negative electrode current collector 21 is made of, for example, a material that does not react with lithium, i.e., does not form any alloy or compound. The material constituting the negative electrode current collector 21 is, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), etc., but is not necessarily limited thereto, and any material used as an electrode current collector in the relevant technical field can be used. The negative electrode current collector 21 can be made of one of the above-mentioned metals, or an alloy or coating material of two or more metals. The negative electrode current collector 21 is, for example, in the form of a plate or foil.

[0112] The all-solid-state secondary battery 1 may further include, for example, a thin film containing an element that forms an alloy with lithium on the negative electrode current collector 21. The thin film is disposed between the negative electrode current collector 21 and the negative electrode active material layer 22. The thin film contains, for example, an element that forms an alloy with lithium. The element that forms an alloy with lithium is, for example, gold, silver, zinc, tin, indium, silicon, aluminum, bismuth, etc., but is not necessarily limited thereto, and any element that forms an alloy with lithium in the relevant technical field may be used. The thin film is composed of one of these metals or an alloy of multiple metals. By disposing the thin film on the negative electrode current collector 21, for example, the deposition form of the metal layer 23 deposited between the thin film 24 and the negative electrode active material layer 22 may be further flattened, and the cycle characteristics of the all-solid-state secondary battery 1 may be further improved.

[0113] The thickness of the thin film is, for example, 1 nm to 800 nm, 10 nm to 700 nm, 50 nm to 600 nm, or 100 nm to 500 nm. If the thickness of the thin film is less than 1 nm, the function of the thin film is difficult to be exerted. If the thickness of the thin film is excessively thick, the thin film itself absorbs lithium, the amount of lithium precipitated at the negative electrode decreases, the energy density of the all-solid-state battery decreases, and the cycle characteristics of the all-solid-state secondary battery 1 may decrease. The thin film may be disposed on the negative electrode current collectors 21, 21a, and 21b by, for example, a vacuum deposition method, a sputtering method, a plating method, or the like, but is not necessarily limited to such a method, and any method for forming a thin film in the art may be used.

[0114] A method for preparing a solid ionic conductor compound according to an embodiment of another aspect includes contacting a lithium precursor compound, a compound containing elements Na, K, Rb, Cs, Fr or a combination thereof, a compound containing phosphorus (P), a compound containing Cl, and a compound containing one or more of elements Br and I to obtain a mixture, and heat-treating the mixture in an inert atmosphere to obtain a solid ionic conductor compound. The solid ionic conductor compound is the solid ionic conductor compound described above.

[0115] The lithium precursor compound can include lithium sulfide, for example, Li2S.

[0116] The compounds containing the elements Na, K, Rb, Cs, Fr or combinations thereof are also halides and sulfides of the elements Na, K, Rb, Cs, Fr or combinations thereof. For example, the compounds containing the elements Na, K, Rb, Cs, Fr or combinations thereof are also NaCl, KCl, NaBr, KI, Na2S, K2S, Rb2S, etc.

[0117] The compound containing P includes phosphorus sulfides, such as P2S5.

[0118] The compound containing Cl is, for example, LiCl.

[0119] The compound containing one or more of the elements Br and I is, for example, LiBr or LiI.

[0120] According to an embodiment, the mixture may further include a compound containing the elements Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or a combination thereof, such as a sulfide of one or more of the elements. For example, the mixture may include GeS2, etc.

[0121] Such compounds can be prepared by contacting the starting materials in suitable amounts, e.g., stoichiometric amounts, to form a mixture, and heat-treating the mixture. Contacting can include, for example, milling, such as ball milling, or grinding.

[0122] The stoichiometric mixture of precursors can be heat treated in an inert atmosphere to produce the solid ionic conductor compound.

[0123] The heat treatment can be performed at, for example, 400 to 700°C, 400 to 650°C, 400 to 600°C, 400 to 550°C, or 400 to 500°C. The heat treatment time can be, for example, 1 to 36 hours, 2 to 30 hours, 4 to 24 hours, 10 to 24 hours, or 16 to 24 hours. The inert atmosphere is an atmosphere containing an inert gas. The inert gas is, for example, nitrogen, argon, etc., but is not necessarily limited thereto, and any gas that is used as an inert gas in the technical field can be used.

[0124] The present invention will be described in more detail through the following examples and comparative examples, however, the examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention.

[0125] (Production of solid ionic conductor compounds) Example 1: Li 5.6 Na 0.05 P.S. 4.65 Cl 1.25 I 0.1 In a glove box under an Ar atmosphere, the lithium precursor LiS, the phosphorus (P) precursor PS, the sodium (Na) precursor NaS, the chlorine (Cl) precursor LiCl, and the iodine (I) precursor LiI were mixed to obtain a Li precursor having a desired composition. 5.6 Na 0.05 P.S. 4.65 Cl 1.25 I 0.1 The mixture was then crushed and mixed in a planetary ball mill containing zirconia (YSZ) balls in an Ar atmosphere at 100 rpm for 1 hour, and then crushed and mixed at 800 rpm for 30 minutes to obtain a mixture. The mixture was pressed under uniaxial pressure to prepare pellets with a thickness of about 10 mm and a diameter of about 13 mm. The prepared pellets were covered with gold foil and placed in a carbon crucible, which was then vacuum sealed using a quartz glass tube. The vacuum sealed pellets were heated from room temperature to 500°C at a rate of 1.0°C / min in an electric furnace, heat-treated at 500°C for 12 hours, and cooled to room temperature at a rate of 1.0°C / min to produce a solid ion conductor compound.

[0126] The composition of the produced solid ionic conductor compound was Li 5.6 Na 0.05 P.S. 4.65 Cl 1.25 I 0.1 (The ratio of Na substituted in the Li site was 0.01, and the ratio of total halogen elements substituted in the S site was 1.35, (Cl:I=12.5:1)).

[0127] Example 2: Li 5.47 Na 0.03 P.S.4.5 Cl 1.4 I 0.1 The same method as in Example 1 was carried out to produce Li, except that the stoichiometric mixture ratio of the starting materials was changed so that the ratio of Na substituted in the Li site was 0.03 and the ratio of the total halogen elements substituted in the S site was 1.5 (Cl:I = 14:1). 5.47 Na 0.03 P.S. 4.5 Cl 1.4 I 0.1 A solid ion conductor compound having the following composition was produced: (ratio of Na substituted in Li sites: 0.03, ratio of total halogen elements substituted in S sites: 1.5 (Cl:I=14:1)).

[0128] Example 3: Li 5.47 Na 0.03 P.S. 4.5 Cl 1.4 Br 0.1 The same method as in Example 1 was carried out to produce Li, except that the stoichiometric mixture ratio of the starting materials was changed so that the ratio of Na substituted in the Li site was 0.03, the bromine (Br) precursor LiBr was used instead of the iodine (I) precursor, and the ratio of the total halogen elements substituted in the S site was 1.5 (Cl:Br = 14:1). 5.47 Na 0.03 P.S. 4.5 Cl 1.4 Br 0.1 A solid ion conductor compound having the following composition was produced: (ratio of Na substituted in Li sites: 0.03, ratio of total halogen elements substituted in S sites: 1.5 (Cl:Br=14:1)).

[0129] Example 4: Li 5.37 Na 0.03 P.S. 4.4 Cl 1.4 Br0.2 The same method as in Example 1 was carried out to produce Li, except that the stoichiometric mixture ratio of the starting materials was changed so that the ratio of Na substituted in the Li site was 0.03, the bromine (Br) precursor LiBr was used instead of the iodine (I) precursor, and the ratio of the total halogen elements substituted in the S site was 1.6 (Cl:Br = 7:1). 5.37 Na 0.03 P.S. 4.4 Cl 1.4 Br 0.2 A solid ion conductor compound having the following composition was produced: (ratio of Na substituted in Li sites: 0.03, ratio of total halogen elements substituted in S sites: 1.6 (Cl:Br=7:1)).

[0130] Example 5: Li 5.57 Na 0.03 P 0.9 Ge 0.1 S 4.5 ClBr 0.5 In a glove box under an Ar atmosphere, the lithium precursor LiS, the phosphorus (P) precursor P2S5, the sodium (Na) precursor NaS, the germanium (Ge) precursor GeS, the chlorine (Cl) precursor LiCl, and the bromine (Br) precursor LiBr were mixed to prepare Li 5.57 Na 0.03 P 0.9 Ge 0.1 S 4.5 ClBr 0.5The mixture was then crushed and mixed in a planetary ball mill containing zirconia (YSZ) balls in an Ar atmosphere at 100 rpm for 1 hour, and then crushed and mixed at 800 rpm for 30 minutes to obtain a mixture. The mixture was pressed under uniaxial pressure to prepare pellets with a thickness of about 10 mm and a diameter of about 13 mm. The prepared pellets were covered with gold foil and placed in a carbon crucible, which was then vacuum-sealed using a quartz glass tube. The vacuum-sealed pellets were heated from room temperature to 500°C at a rate of 1.0°C / min in an electric furnace, heat-treated at 500°C for 12 hours, and cooled to room temperature at a rate of 1.0°C / min to produce a solid ion conductor compound.

[0131] The composition of the produced solid ionic conductor compound was Li 5.57 Na 0.03 P 0.9 Ge 0.1 S 4.5 ClBr 0.5 (The ratio of Na substituted in the Li site was 0.03, the ratio of Ge substituted in the P site was 0.1, and the ratio of total halogen elements substituted in the S site was 1.5, (Cl:Br=2:1)).

[0132] Example 6: Li 5.37 Na 0.03 P.S. 4.4 Cl 0.8 Br 0.8 The same method as in Example 1 was carried out to produce Li, except that the ratio of Na substituted in the Li site was 0.03, the bromine (Br) precursor LiBr was used instead of the iodine (I) precursor, and the stoichiometric mixture ratio of the starting materials was changed so that the ratio of the total halogen elements substituted in the S site was 1.6 (Cl:Br = 1:1). 5.37 Na 0.03 P.S. 4.4 Cl 0.8 Br 0.8A solid ion conductor compound having the following composition was produced: (ratio of Na substituted in Li sites: 0.03, ratio of total halogen elements substituted in S sites: 1.6 (Cl:Br=1:1)).

[0133] Comparative example 1: Li 6 P.S. 5 Cl A solid ionic conductor compound was prepared in the same manner as in Example 1, except that Na2S and LiI were not added and the stoichiometric mixture ratio of the starting materials was changed to obtain the desired composition Li6PS5Cl.

[0134] The composition of the produced solid ionic conductor compound was Li6PS5Cl.

[0135] Comparative example 2: Li 5.4 P.S. 4.4 Cl 1.6 The desired composition is Li 5.4 P.S. 4.4 Cl 1.6 A solid ionic conductor compound was produced in the same manner as in Example 1, except that Na2S and LiI were not added and the stoichiometric mixing ratio of the starting materials was changed so that

[0136] The composition of the produced solid ionic conductor compound was Li 5.4 P.S. 4.4 Cl 1.6 It was.

[0137] Comparative example 3: Li 5.37 Na 0.03 P.S. 4.4 Cl 0.2 Br 1.4 The desired composition is Li 5.37 Na 0.03 P.S. 4.4 Cl 0.2 Br 1.4A solid ionic conductor compound was prepared in the same manner as in Example 1, except that the stoichiometric mixture ratio of the starting materials was changed by using LiBr instead of LiI so as to obtain:

[0138] The composition of the produced solid ionic conductor compound was Li 5.37 Na 0.03 P.S. 4.4 Cl 0.2 Br 1.4 It was.

[0139] Comparative example 4: Li 5.37 Na 0.03 P.S. 4.4 Cl 1.6 The desired composition is Li 5.37 Na 0.03 P.S. 4.4 Cl 1.6 A solid ionic conductor compound was produced in the same manner as in Example 1, except that LiI was not added and the stoichiometric mixing ratio of the starting materials was changed so as to obtain the above.

[0140] The composition of the produced solid ionic conductor compound was Li 5.37 Na 0.03 P.S. 4.4 Cl 1.6 It was.

[0141] Comparative example 5: Li 5.4 P.S. 4.4 Cl 1.4 Br 0.2 The desired composition is Li 5.4 P.S. 4.4 Cl 1.4 Br 0.2 A solid ion conductor compound was produced in the same manner as in Example 1, except that Na2S was not added and LiBr was added instead of LiI to change the stoichiometric mixture ratio of the starting materials so that

[0142] The composition of the produced solid ionic conductor compound was Li 5.4 P.S. 4.4 Cl 1.4 Br 0.2 It was.

[0143] Example 7: Production of all-solid-state secondary battery (Positive electrode layer manufacturing) The solid ion conductor compound prepared in Example 1 was pulverized in a pot mill at 150 rpm for 15 hours to obtain an average particle size (D 50 ) A positive electrode solid electrolyte having a particle size of 1 to 2 μm was formed. The positive electrode solid electrolyte and the large-particle positive electrode active material LiNi 0.8 Co 0.15 Al 0.05 O2(NCA)(D 50 =14μm), small-particle positive electrode active material LiNi 0.8 Co 0.15 Al 0.05 O2(NCA)(D 50 =5μm), carbon nanofibers as a conductive material, and polytetrafluoroethylene as a binder were mixed together, and xylene was added to the mixture to obtain a positive electrode layer composition, which was then kneaded and formed into a sheet to manufacture a positive electrode sheet. The mixing ratio of the large particle positive electrode active material to the small particle positive electrode active material was 3:1, and the mixing ratio of the positive electrode active material, conductive material, binder, and solid electrolyte was 84:0.2:1.0:14.8 by weight. The positive electrode sheet was pressed onto an 18μm thick aluminum foil positive electrode current collector, placed in a batch type oil chamber, and subjected to a warm isostatic press process at a pressure of 500mPa to form a compressed positive electrode layer.

[0144] (Electrolyte layer production) The solid ion conductor compound prepared in Example 1 was pulverized in a pot mill at 150 rpm for 8 hours to obtain an average particle size (D 50) A powder of 3 to 4 μm was formed, and an acrylic resin as a binder was added to the electrolyte powder in a weight ratio of 98.5:1.5 to prepare a mixture. A solvent IBIB was added to the mixture and stirred to produce a composition for forming an electrolyte layer. The composition for forming a solid electrolyte layer was placed on a polyethylene nonwoven fabric, a blade was moved, and the mixture was dried in air at 25°C for 12 hours, and then vacuum dried at 70°C for 2 hours to form a sheet-like solid electrolyte layer formed on the polyethylene nonwoven fabric.

[0145] (Negative electrode layer manufacturing) A SUS foil (thickness: 10 μm) was prepared as a negative electrode current collector. Silver (primary particle size: 60 nm) and carbon black powder (primary particle size: 35 nm) were mixed in a weight ratio of 25:75 to prepare a negative electrode active material. The silver (primary particle size: 60 nm) and carbon black powder (primary particle size: 35 nm) were put into a container together with polyvinylidene fluoride binder at 7% by weight based on the negative electrode layer in N-methylpyrrolidone (NMP), and stirred to prepare a slurry for forming the negative electrode layer. The slurry for forming the negative electrode layer was applied to the SUS foil using a blade coater, dried in air at a temperature of 80° C. for 20 minutes, and vacuum dried at 100° C. for 12 hours to prepare a negative electrode layer.

[0146] (Manufacturing all-solid-state secondary batteries) The positive electrode layer, the electrolyte layer, and the negative electrode layer obtained by the above process were sequentially stacked, and the stacked layers were subjected to a hydrostatic press at 85° C. and a pressure of 500 MPa for about 30 minutes to prepare an all-solid-state secondary battery.

[0147] Examples 8 to 12 All-solid-state secondary batteries were manufactured in the same manner as in Example 7, except that the solid electrolyte powder manufactured in Examples 2 to 6 was used instead of the solid electrolyte powder manufactured in Example 1.

[0148] Comparative Examples 6 to 10 All-solid-state secondary batteries were manufactured in the same manner as in Example 7, except that the solid electrolyte powders manufactured in Comparative Examples 1 to 5 were used instead of the solid ion conductor compound powder manufactured in Example 1.

[0149] Evaluation example 1: Ionic conductivity evaluation The solid ion conductor compounds prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were ground in an agate mortar to prepare powders, and then 200 mg of the powders were mortared at 4 ton / cm 2 A pellet specimen with a thickness of about 0.900 mm and a diameter of about 13 mm was prepared by pressing the specimen at a pressure of 1000 MPa for 2 minutes. A symmetry cell was prepared by disposing indium (In) electrodes with a thickness of 50 μm and a diameter of 13 mm on both sides of the prepared specimen. The preparation of the symmetric cell was carried out in a glove box with an Ar atmosphere.

[0150] The impedance of the pellet was measured by the two-probe method using an impedance analyzer (Material Mates 7260 impedance analyzer) for a specimen with indium electrodes on both sides. The frequency range was 0.1Hz to 1MHz, and the amplitude voltage was 10mV. The measurements were performed at 25°C in an Ar atmosphere. The resistance was obtained from the arc of the Nyquist plot for the impedance measurement results, and the ionic conductivity was calculated taking into account the area and thickness of the specimen.

[0151] The results of the ionic conductivity measurements are shown in Table 1.

[0152] [Table 1]

[0153] As shown in Table 1, Examples 1 to 6 of the present invention show ion conductivities of 3.4 mS / cm or more, and therefore can be suitably used as solid electrolytes for all-solid-state batteries.

[0154] Evaluation example 2: Crystal structure evaluation The solid ionic conductor compounds prepared in Examples 1 to 6 and Comparative Example 3 were pulverized in an agate mortar to prepare powders, and the powder XRD spectrum was measured. The results are shown in FIG. 1.

[0155] Referring to FIG. 1, the peak intensity at 2θ=29.07°±0.5° is I B and the peak intensity at 2θ = 30.09° ± 0.5° is defined as I A If we define I B / I A The values ​​were calculated and are shown in Table 2 below.

[0156] [Table 2]

[0157] Referring to FIG. 1 and Table 2, it was confirmed that when the ratio of Cl to Br exceeds 1:1 and the molar fraction of Br is greater than the molar fraction of Cl (Comparative Example 3), the ratio of impurities increases sharply.

[0158] Evaluation example 3: Softness evaluation The solid ion conductor compounds of Examples 1 to 3 and Comparative Examples 1, 2, 4, and 5 were ground in an agate mortar to prepare powders, and the powder densities (ρ a ) and pellet density (ρ b ) was calculated and is shown in Figure 2.

[0159] The powder density is a theoretical value calculated from the most stable structure obtained by the first-principles calculation software VASP, and the pellet density is 4 ton / cm after processing 200 mg of the powder into a pellet with a diameter of 13 mm. 2 After pressing for 2 minutes at a pressure of 1000 g, the thickness was measured and the pellet weight (200 mg) was converted into a volume (π(13 mm / 2) 2 × measured thickness).

[0160] Referring to FIG. 2, it was confirmed that the solid ion conductor compounds of Examples 1 to 3 containing Na, Cl, and (Br or I) had improved pellet density / powder density ratios compared to the compounds containing only Cl without Na (Comparative Examples 1 and 2), Na and one halogen element (Comparative Example 4), and the compounds containing only Cl and Br (Comparative Example 5).

[0161] A high pellet density / powder density ratio suggests that the solid ion conductor compound has excellent contact with different all-solid-state battery materials, and it was confirmed that the inclusion of Na and Cl (Br or I) provides excellent flexibility compared to the inclusion of only Na, only Cl, or two halogens (Cl and Br).

[0162] Evaluation example 4: High rate characteristic evaluation The high rate characteristics of the all-solid-state secondary batteries prepared in Example 7 and Comparative Example 7 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the all-solid-state secondary batteries in a chamber at 45°C. Each all-solid-state secondary battery was charged at a constant current of 0.1C and a constant voltage of 4.25V until the current value reached 0.05C. Then, the battery was discharged at a constant current of 0.05C until the battery voltage reached 2.5V, and discharged to 2.5V. Thereafter, the battery was charged at constant currents of 0.1C, 0.1C, 0.1C, and 0.33C and a constant voltage of 4.25V, and then discharged at constant currents of 0.1C, 0.33C, 1C, and 0.33C, respectively, to observe the change in discharge capacity.

[0163] The discharge capacity and discharge capacity retention rate according to the discharge rate of the all-solid-state secondary batteries prepared in Example 7 and Comparative Example 7 are shown in FIGS. 3A and 3B, respectively.

[0164] It can be seen that the all-solid-state secondary battery of Example 7 had a 0.33C reference discharge capacity (177 mAh / g) that was increased by about 5% compared to the discharge capacity of the all-solid-state secondary battery of Comparative Example 7 (168 mAh / g).

[0165] In addition, the all-solid-state secondary battery of Example 7 had an average 1C / 0.33C discharge capacity realization rate of 92%, which was improved in rate capability compared to 74% for the all-solid-state secondary battery of Comparative Example 7.

[0166] Evaluation example 5: Moisture stability evaluation The solid ion conductor compounds manufactured in Example 5 and Comparative Example 1 were pulverized in an agate mortar to prepare 30 mg of powder (D50 ≒ 18 μm), which was then placed in a chamber with an air atmosphere at 19°C and RH 60%, and the amount of H2S gas generated in the chamber was measured for 0 to 300 minutes.

[0167] The measured results are shown in FIG.

[0168] [Table 3]

[0169] 4 and Table 3, it was confirmed that the solid ion conductor compound of Example 5 has improved stability against moisture due to the introduction of different halogen elements Cl and Br and Ge, and the amount of H2S generated by the side reaction of S element in the crystal was significantly reduced. It was confirmed that the ratio of H2S gas generated after 300 minutes was reduced by about 48% in the solid ion conductor compound of Example 5 compared to the solid ion conductor compound of Comparative Example 1.

[0170] Evaluation example 6: Life characteristic evaluation The charge / discharge test of the all-solid-state secondary batteries prepared in Example 7 and Comparative Example 7 was performed by placing the all-solid-state secondary batteries in a chamber at 45°C.

[0171] In the first cycle, the battery was charged at a constant current of 0.33 C and a constant voltage of 4.25 V until the battery voltage reached 4.25 V, at a current value of 0.05 C. Then, the battery was discharged at a constant current of 0.33 C until the battery voltage reached 2.5 V.

[0172] Thereafter, the same charge and discharge cycle was performed 510 times, and the charge and discharge curves at the first and 100th cycles were recorded, and the discharge capacity at each cycle was measured and shown in FIGS. 5 and 6, respectively.

[0173] Referring to FIG. 5, it can be seen that the all-solid-state secondary battery of Example 7 has stable charge / discharge characteristics even after 100 cycles, while the all-solid-state secondary battery of Comparative Example 7 shows a voltage drop and an increase in internal resistance after 100 cycles.

[0174] Referring to FIG. 6, it was confirmed that the all-solid-state secondary battery of Example 7 exhibited a capacity retention rate of 80% or more even after 510 or more charge / discharge cycles, and it was confirmed that the all-solid-state secondary battery of Comparative Example 7 was short-circuited after 150 cycles.

[0175] Therefore, it was confirmed that the all-solid-state secondary battery of Example 7 had stable charge / discharge characteristics and excellent life characteristics.

[0176] Although the preferred embodiment of the present invention has been described above with reference to the drawings and examples, it will be understood that the present invention is merely illustrative and that various modifications and equivalent embodiments are possible by those skilled in the art. Therefore, the scope of the present invention should be determined by the claims.

Claims

1. It is represented by the following chemical formula 1: A solid ionic conductor compound having the argyrodite crystal structure: Li a M x T y P b S c Cl d X e (Chemical formula 1) In the above Chemical Formula 1, M is Na, K, Rb, Cs, Fr or a combination thereof; T is Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or a combination thereof; X is Br, I or a combination thereof; 4<a<7, 0<x<1, 0<y<1, 0<b≦1, 4<c≦5, 1≦d+e<2, and 1≦d / e.

2. 2. The solid ionic conductor compound of claim 1 , wherein 0<x≦0.

5.

3. 2. The solid ionic conductor compound of claim 1 , wherein 0<y<0.

5.

4. 2. The solid ionic conductor compound of claim 1 , wherein 1.3≦d+e<2.

5. 2. The solid ionic conductor compound of claim 1, wherein 1≦d / e<18.

6. The solid ionic conductor compound has a peak intensity (I B ) and the peak intensity at 2θ = 30.09° ± 0.5° (I A ) ratio (I B / I A ) is I B / I A 2. The solid ionic conductor compound of claim 1, wherein R is a stoichiometric ratio of 1:1 or 2:

1.

7. I B / I A I B / I A 7. The solid ionic conductor compound of claim 6, wherein ≦0.

1.

8. The solid ionic conductor compound according to claim 1 , wherein the chemical formula 1 is represented by the following chemical formula 2: (Li 1-x1 M1 x1 ) 7+α-β (P 1-y1 T1 y1 ) α S 6-β (Cl 1-e1 X1 e1 ) β (Chemical formula 2) In the above Chemical Formula 2, M1 is Na, K, Rb, Cs, Fr or a combination thereof; T1 is Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or a combination thereof; X1 is Br, I or a combination thereof; 0<x1<1, 0<y1<1, 0<e1≦0.5, 0<α≦1, and 0<β≦2.

9. 9. The solid ionic conductor compound of claim 8, wherein M1 is Na, K or a combination thereof.

10. 9. The solid ionic conductor compound of claim 8, wherein y1 is 0<y1≦0.5 and T1 is Ge.

11. 9. The solid ionic conductor compound of claim 8, wherein X1 is Br.

12. 9. The solid ionic conductor compound of claim 8, wherein β is in the range of 1≦β≦2.

13. The solid ionic conductor compound according to claim 1 , wherein the chemical formula 1 is represented by the following chemical formula 3: Li 7-x2+y2-d2-e2 M2 x2 P 1-y2 T2 y2 S 6-d2-e2 Cl d2 X e2 (Chemical formula 3) In the above Chemical Formula 3, M2 is Na, K, Rb, Cs, Fr or a combination thereof; T2 is Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or a combination thereof; X2 is Br, I or a combination thereof; 0<x2<1, 0<y2<1, 1≦d2+e2<2, and d2 / e2≧1.

14. 14. The solid ionic conductor compound of claim 13, wherein 0<x2≦0.5, 0<y2<0.5, and 1.3≦d2+e2<2.

15. 14. The solid ionic conductor compound of claim 13, wherein 0.8≦d2<2 and 0<e2≦0.

8.

16. The solid ionic conductor compound is Li 5.57 Na 0.03 P 0.9 Ge 0.1 S 4.5 ClBr 0.5 , Li 5.57 Na 0.03 P 0.9 Ge 0.1 S 4.5 C 0.8 B 0.7 , Li 5.57 Na 0.03 P 0.8 Ge 0.2 S 4.5 C 1.4 I 0.1 Or Li 5.57 Na 0.03 P 0.8 S 0.2 S 4.4 C 1.4 B 0.2 2. The solid ionic conductor compound of claim 1 ,

17. 10. The solid ionically conductor compound of claim 1, wherein the solid ionically conductor compound has a pellet density / powder density ratio of 85% or more.

18. A solid electrolyte comprising the solid ion conductor compound according to any one of claims 1 to 17.

19. a positive electrode layer including a positive electrode active material layer; a negative electrode layer including a negative electrode active material layer; an electrolyte layer disposed between the positive electrode layer and the negative electrode layer; Electrochemical cell comprising a solid ionically conductor compound according to any one of claims 1 to 17.

20. 20. The electrochemical cell of claim 19, wherein the positive electrode active material layer comprises the solid ionically conductor compound.

21. The solid ion conductor compound has an average particle size (D 50 21. The electrochemical cell of claim 20 having

22. 20. The electrochemical cell of claim 19, wherein the electrolyte layer comprises the solid ionically conductor compound.

23. The solid ion conductor compound has an average particle size (D 50 23. The electrochemical cell of claim 22 having

24. 20. The electrochemical cell of claim 19, wherein the positive electrode active material layer and the electrolyte layer comprise the solid ionically conductor compound.

25. 20. The electrochemical cell of claim 19, wherein the electrochemical cell is an all-solid-state secondary battery.

26. The negative electrode active material layer includes a negative electrode active material and a binder, 20. The electrochemical cell of claim 19, wherein the negative electrode active material is a mixture of amorphous carbon and one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn).

27. The negative electrode layer includes a negative electrode current collector, The negative electrode further includes a metal layer disposed between the negative electrode current collector and the negative electrode active material layer, 20. The electrochemical cell of claim 19, wherein the metal layer comprises lithium or a lithium alloy.

28. contacting a lithium precursor compound; a compound containing the elements Na, K, Rb, Cs, Fr or combinations thereof; a phosphorus (P) containing compound; a Cl containing compound; and a compound containing one or more of the elements Br and I to provide a mixture; and heat treating the mixture in an inert atmosphere to provide a solid ionic conductor compound.

13. A method for producing a solid ionic conductor compound, wherein the mixture further comprises a compound comprising the elements Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, Bi, or combinations thereof.

29. The method for producing a solid ionically conductor compound according to claim 28, wherein the heat treatment is carried out at a temperature of 400° C. to 700° C. for 1 to 36 hours.

Citation Information

Patent Citations

  • Solid electrolyte, all-solid battery, and method for manufacturing solid electrolyte

    JP2017117753A

  • Sulfide solid electrolyte

    WO2018047565A1

  • Metal element-containing sulfide-type solid electrolyte and method for producing same

    WO2019098245A1